Chemical tuning of electronic structure of germanium nanowires using density functional theory - Kuah, Kwok Jian. (2010)
Societal continued demand for faster and more compactness to life’s everyday solutions have shifted scientists’ attention to create one-dimensional nanostructure called nanowires (NW), materials touted to be the building blocks for future device and bring about new possibilities. The understanding of nanotechnology is still in its infancy but promising device performance has already been demonstrated on prototype biosensor and field-effect-transistor (FET) applications. Semiconductor silicon had been the material of choice in electronic devices, but the observation of silicon reaching its intrinsic property limits have renewed interest in germanium (Ge) for mainstream use. In order to achieve oxidation protection and electronic property manipulation, the structural and electronic properties due to different passivation chemical species on GeNW are investigated using density functional theory. The results show bandgap reduction capacity in the order of species –SCH3 > -Cl, -Br > -CH3 with alkyl and alkanethiol species displaying conductance and valance band shifting as well which can result in bandgap nature change from direct to indirect. Stability studies through binding and formation energies calculations reveals greater NW stability compared to H-GeNW with a new postulation that long passivation alkyl chain having a dominating contribution to NW oxidation resistance. The final analysis suggest alkanethiol to provide the strongest combination of oxidation resistance and bandgap manipulation to GeNW, thus proving to be the most promising passivation species for future high performance electronic devices.